Tình hình đề kháng kháng sinh của các chủng vi khuẩn Staphylococcus aureus phân lập tại Bệnh viện Trường Đại học Y - Dược Huế (3/2022- 3/2023) - Nguyễn, Thị Châu Anh; Hoàng, Như Quỳnh; Nguyễn, Đức Hoàng Sang; Nguyễn, Thị Tuyền; Hoàng, Thị Minh Ngọc; Dương, Thị Ngọc Mai; Nguyễn, Thị Khánh Linh (Tạp chí Y Dược Huế, 2024)
Background: Staphylococcus aureus is one of the major causes of infections in hospitals. Many studies have pointed out the fact that Staphylococcus aureus is resistant to many antibiotics, especially Methicillin- Resistant Staphylococcus aureus (MRSA). Objectives: To determine the frequency of Staphylococcus aureus and the frequency of the antibiotic resistance of S. aureus strains isolated at Hue University of Medicine and Pharmacy Hospital 2022. Materials and methods: A cross-sectional descriptive study on S. aureus strains isolated at Hue University of Medicine and Pharmacy Hospital from March 2022 to March 2023, determining antibiotic resistance by Kirby-Bauer technique. Results: The frequency of S. aureus infections is 18.0%. The frequency of MRSA infections was 61.7%, the antibiotic resistance rates of S. aureus strains were the highest in the beta-lactam antibiotic group (61.7% - 95.8%), followed by erythromycin 65.1%, clindamycin (59.9%). The rates of resistance of MRSA to penicillin, erythromycin, clindamycin, trimethoprim-sulfa antibiotics were higher than that of MSSA and this difference was statistically significant (p < 0.05). The rate of multi-resistance to over 6 antibiotics of MRSA accounted for 9.3%. Conclusion: The frequency of S. aureus infections was 18.0%. The rate of MRSA accounts for 61.7%, the rate of multi-antibiotic resistant MRSA (over 6 antibiotics) was low, with 9.3%